2022
DOI: 10.1007/s00068-022-01887-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of key factors influencing treatment strategy and outcome of fragility fractures of the pelvis (FFP)

Abstract: Background Fragility fractures of the pelvis (FFP) are a clinical entity with an increasing significance in clinical practice. Little is known about the conditions, which influence decision making and outcome. Setting Level I trauma center. Material and methods Prospective assessment of selected parameters of patients, who were admitted with a FFP in a 2-year period. Fractures were classified in accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…[68] In their prospective study on 110 patients, Rommens et al worked out that the degree of pelvic instability, late presentation, and failure of conservative treatment were key factors for the indication of operative treatment. [66] The last studies endorse the original recommendations for surgical treatment published by Rommens and Hofmann in 2013. [21,69]…”
Section: Outcomementioning
confidence: 79%
See 1 more Smart Citation
“…[68] In their prospective study on 110 patients, Rommens et al worked out that the degree of pelvic instability, late presentation, and failure of conservative treatment were key factors for the indication of operative treatment. [66] The last studies endorse the original recommendations for surgical treatment published by Rommens and Hofmann in 2013. [21,69]…”
Section: Outcomementioning
confidence: 79%
“…Nevertheless, there is no difference found in mobility and independence between operatively and conservatively treated patients in several studies. [65,66] In the series of Schmitz et al, quality of life and mobility were even higher in the conservative group. [67] On the contrary, large case series indicate that mortality is lower in operatively treated patients.…”
Section: Outcomementioning
confidence: 89%
“…With a comparable distribution of FFP types, Rommens et al [ 75 ] also found a lower mortality in surgically treated patients. The one-year mortality rate of surgically treated patients with FFP types II-IV was halved in comparison with conservatively treated patients [ 76 ]. As in our case, surgically treated patients benefit from minimally invasive percutaneous procedures in terms of complication rate and mortality [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…While all fragility fractures carry associated complications, FFP carry a significant one year mortality risk of 16.7–19 % from different sources, rising to 22 %–27 % with increasing age or residence in a nursing home [6] . Reduction in mortality rate is centralized upon early mobilization, decreasing the multifold complications associated with prolonged bed rest in the elderly population [4] . Many of these pelvic fractures are treated conservatively with nonoperative management, pain control, and weight bearing as tolerated.…”
Section: Introductionmentioning
confidence: 99%